2016
DOI: 10.1080/1828051x.2016.1202735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Italian heavy pig diets based on different barley varieties with or without non-starch polysaccharides degrading enzymes on growth performance, carcass characteristics and fresh thigh quality

Abstract: The effect of diets based on two different barley varieties, with or without non-starch polysaccharides (NSP) degrading enzymes was evaluated on growth performance, carcass characteristics and fresh thigh quality in Italian heavy growing-finishing pigs. Pigs (64) were assigned to four diets: two diets based on 85% of hulled normal-amylose barley (Cometa, with or without NSP enzyme complex) and two diets based on 85% of hulless low-amylose barley (Alamo, with or without NSP enzyme complex). The diets were formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Doti et al (2014) reported similar results: these authors found in vitro comparable levels of resistant starch in a pig diet based on pea as starch source, compared to other experimental on cerealsbased diets. Previous studies (Prandini et al 2015(Prandini et al , 2016 reported that the starch sources rich in amylopectin and soluble starch increase the feed efficiency and growth performance in pigs. In some cereals and legumes, the starch granules have adjacent proteins in the endosperm, or sometimes indented in the starch surface, thus providing a continuous protein matrix, that plays as further barrier against amylase (Berg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Doti et al (2014) reported similar results: these authors found in vitro comparable levels of resistant starch in a pig diet based on pea as starch source, compared to other experimental on cerealsbased diets. Previous studies (Prandini et al 2015(Prandini et al , 2016 reported that the starch sources rich in amylopectin and soluble starch increase the feed efficiency and growth performance in pigs. In some cereals and legumes, the starch granules have adjacent proteins in the endosperm, or sometimes indented in the starch surface, thus providing a continuous protein matrix, that plays as further barrier against amylase (Berg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This multienzyme preparation significantly improved the activities of related digestive enzymes in the intestines of these pigs and their growth performance [ 25 ]. Du et al found that compared with single enzyme preparations, compound enzyme preparations had a better effect on the growth performance of weaned piglets and the utilization rate of nitrogen and phosphorus [ 26 ]. Ai et al reported that NSP enzymes can inhibit the secretion of growth- and metabolism-related hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The raw tags were quality-ltered under speci c ltering conditions to obtain high-quality clean tags [14] according to QIIME (Version 1.9.1) 2 [12] quality control process. Next, the tags were compared with the reference database (Silva database) 3 by using the UCHIME algorithm 4 to detect chimera sequences, which were then removed [15][16] . Then, the effective tags were nally obtained.…”
Section: Bioinformatics Analysesmentioning
confidence: 99%
“…A compound enzyme preparation is composed of one or several single enzyme preparations as the main body, mixed with other single enzyme preparations, or obtained through fermentation by one or several microorganisms. Studies have shown that adding a compound enzyme preparation to the feed can supplement the lack of endogenous enzyme secretion, effectively reduce the level of antinutritional factors in feed, improve the feed nutritional value, and promote the healthy growth of animals [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%